Differences in quality parameters between types of commercial tea from Argentina - Thea, Ana Eugenia (2012)
To determine differences in quality parameters between different types of tea elaborated in Argentina, water extract, crude fibre, caffeine, total polyphenol content, antioxidant activity, sorption isotherms and colour parameters (L, a, b) were determined. Fifty-one industrial samples of commercially available teas including green tea, semifermented tea, black tea and black tea sub-product (BTSP) were used for this study.Water extract contents were significantly higher in black tea and green tea (40.3% and 40.7% w/w, respectively), while semifermented tea and BTSP showed higher levels of crude fibre (22.3% and 20.4% w/w, respectively). Caffeine contents of black teas (2.7% w/w) were significantly higher than in the other types of tea. Green teas revealed the highest concentrations of phenolic compounds and the major antioxidant activities (14.9 g GAE/100g dm and 30.0 g AAE/100g dm, respectively). The results also highlighted significant differences (p<0.05) in colour values between the different types of tea.